1999
DOI: 10.1007/s004170050319
|View full text |Cite
|
Sign up to set email alerts
|

Complications after implantation of intraocular devices in patients with cytomegalovirus retinitis

Abstract: In the treatment of CMV retinitis, sustained-release ganciclovir implantation seems to be an alternative to intravenous ganciclovir. Early implantation and additional replacement of the device has the potential to decrease the risk of developing retinal detachment. We would recommend additional systemic antiviral CMV therapy to avoid infection of the fellow eye and CMV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The implantation of sustainedrelease devices into the vitreous offers an alternative strategy but is associated with similar adverse effects. 31 In contrast, local gene transfer offers the possibility of targeted and sustained delivery of therapeutic agents following a single procedure. In this study we show that localised expression of sFlt-1 by gene transfer inhibits retinal neovascularisation in a murine model of ischaemic retinopathy and demonstrate the feasibility of a gene transfer approach to the control of angiogenesis in retinal neovascular disorders.…”
Section: And Iris Pigment Epithelium Aav-mediated Gfp Expression Wasmentioning
confidence: 99%
“…The implantation of sustainedrelease devices into the vitreous offers an alternative strategy but is associated with similar adverse effects. 31 In contrast, local gene transfer offers the possibility of targeted and sustained delivery of therapeutic agents following a single procedure. In this study we show that localised expression of sFlt-1 by gene transfer inhibits retinal neovascularisation in a murine model of ischaemic retinopathy and demonstrate the feasibility of a gene transfer approach to the control of angiogenesis in retinal neovascular disorders.…”
Section: And Iris Pigment Epithelium Aav-mediated Gfp Expression Wasmentioning
confidence: 99%
“…5,6 However, the application of these devices has involved complications such as cataract, retinal detachment, and vitreous hemorrhage, produced by the implantation of the devices. 7,8 Recently, it has been hypothesized that transscleral delivery may be an effective method of achieving therapeutic concentrations of drugs in the posterior part of the eye. 9 -12 We have recently demonstrated that steroid-loaded biodegradable intrascleral implants can deliver the drug at therapeutic levels in the vitreous and retina-choroid.…”
mentioning
confidence: 99%
“…In approximately 12 %, problems are encountered such as extrusion, vitreous haemorrhage or CMO (Lim et al 1999 ;Guembel et al 1999 ) . This contains 4.5 mg of Gancyclovir, is inserted into the pars plana at 4 mm from the corneo-scleral limbus and may last up to 1 year.…”
Section: For Treatmentmentioning
confidence: 99%